The Impact of Professional Commitment and Anticipatory Socializationon Accounting Students’ Ethical Orientation - Elias, Rafik Z. (Journal of business ethics, 2006)
The accounting profession has emphasized the need for ethics education in the accounting curriculum. The current study examines professional commitment and anticipatory socialization, operationalized by perception of financial reporting, as possible determinants of Accounting students’ ethical perceptions and intentions. Accounting students with higher levels of professional commitment and higher perception of the importance of financial reporting were more likely to perceive questionable actions as unethical and less likely to engage in such actions compared to those students with lower commitment and lower perception of financial reporting. The results have implications for accounting instructors and accounting employers as they socialize students in the accounting profession at this early stage.